ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY PADA PERUSAHAAN PERDAGANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2012 - Zaki Rifki; Zulbahridar -; Elfi Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study was to examine the effect of profitability (ROA), solvency (DER), the reputation of the Public Accounting Firm (KAP), corporate ownership and firm size on audit delay in the trading company. The population in this study are the trading company in Indonesia Stock Exchange (IDX) as many as 36 companies. Observation period is 2011 to 2012. Technique used to determination sample is purposive sampling method, where the sample is determined by certain criteria. Based on the criteria, then there are 30 sample companies. While to analysis the data is using multiple regression analysis. The results of the research are Return on Assets (ROA) and ownership status (Foreign/Domestic) have a significant impact on audit delay. It can be seen from the t value is greater than t - table. Whereas the Debt to Equity Ratio, Public Accounting Firm Reputation and size of the company does not have a significant impact on audit delay. It can be seen from the t value is smaller than the t-table then the independent variable has no effect on the dependent variable.Keywords: Profitability (ROA), Solvency (DER), Reputation Public Accounting Firm (KAP), Corporate Ownership and Firm Size, Audit Delay